Реализация коммуникативной категории «контакт» в юмористическом дискурсе - Самохина, В.А.; Samokhina, V.A. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2014)
Статья посвящена реализации коммуникативной категории “контакт” сквозь призму юмористического дискурса. Специфика, функции контакта рассматриваются в основных фазах юмористического контакта с учетом факторов адресанта и адресата. Особенно акцентируется ведущая роль адресата в установлении юмористического контакта. Стаття присвячена реалізації комунікативної категорії “контакт” крізь призму гумористичного дискурсу. Специфіка, функції контакту розглядаються в базових фазах гумористичного контакту з урахуванням факторів адресанта та адресата. Особливо акцентується провідна роль адресата у встановленні гумористичного контакту. The article is taken up with realization of communicative category “contact” in the light of humorous discourse. Specificity and functions of the category “contact” are reviewed in basic stages of humorous contact concerning factors of the addresser and the addressee. The leading role of the addressee in establishing humorous contact is emphasized.
Realization of the communicative category “contact” in humorous discourse
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics; addresser’s factor; communicative category “contact”; humorous discourse; stages of humorous contact; коммуникативная категория “контакт”; фазы юмористического контакта; фактор адресата; юмористический дискурс